“An Enormous Amount of Human Waste”: Self-esteem, Capitalism, and the US Prison, 1973-1989 - Anaïs Lefèvre (Transatlantica)
The period between the passage of the Rockefeller drug laws in 1973 and the Reagan-era expansion of the War on Drugs in the late 1980s was characterized by the rise of penal punitiveness and the triumph of neoliberal logics; it was also during these years that the concept of “self-esteem” came to be used recurrently in relation to prison work programs. Using articles from major newspapers, transcripts of congressional hearings, political speeches, and publications by prison administrators and criminologists, this article argues that the “self-esteem” concept was exploited by prison administrators to present rehabilitation and labor programs as legitimate and efficient. The concept became a vector of capitalist ideology in a context of rising incarceration rates and growing prominence of neoliberal logics. While the historiography of mass incarceration has explored the rise of punitiveness starting in the mid-1970s, this article suggests that there was also a seemingly benevolent side to the legitimation of the carceral state. It also seeks to add to the understanding of neoliberal transformation by exploring the penetration of neoliberal logics behind bars.